Effectiveness of exercise intervention in improving physical and mental status of patients with alcohol use disorders: A systematic review and meta-analysis. - Jihai Li; Zhidong Zhou; Gang Gao; Liuhong Zang (PLoS ONE)
Objectives This meta-analysis and systematic review examined the effects of an exercise intervention on alcohol dependence and physical and mental states in patients with alcohol use disorder (AUD). Data sources PubMed, Web of Science, Cochrane Library, EBSCO, and Embase. Study inclusion and exclusion criteria Randomized controlled trials published in English from the inception of the database until June 30, 2024, were included. All forms of exercise intervention (aerobic, resistance, yoga, mixed exercise, etc.) were included in the study, using an exercise intervention for patients with AUD and a non-exercise control group. Studies that excluded acute exercise or did not describe a specific intervention program; duplicate publications; review articles, conference articles, etc.; and studies that did not report appropriate outcome metrics. Data extraction This protocol was prepared according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol standard. The risk of bias was assessed via the Cochrane risk-of-bias tool as described by the Cochrane Handbook for Systematic Reviews and Interventions. Data synthesis Alcohol dependence (number of drinks per day, number of drinks per week, AUDIT), physical and mental status [maximal oxygen uptake (VO2 max), resting heart rate, anxiety state, depression state, stress level]. Results Seventeen RCTs with a total of 1,905 patients with alcohol use disorders were included as subjects, and the results revealed that the exercise intervention had a significant effect on alcohol dependence, the number of drinks per day and the AUDIT score, the exercise intervention also had a significant effect on physical and mental status, VO2max, the resting heart rate, the anxiety state, the depression state, and the stress level. High heterogeneity in the number of drinks per day, anxiety, depression and stress outcomes (I2 > 50%), but Egger's test showed no publication bias for all outcome indicators (p > 0.05). Conclusions Exercise intervention can effectively reduce alcohol dependence and significantly improve the physical and mental states of AUD patients, and exercise intervention as an adjunct to the treatment of AUD patients is significantly effective.